Motivational Pathways for Young People to Pursue Postgraduate Studies at Historically Disadvantaged Universities: Insights into Key Motivators and Challenges - Chauke, Thulani Andrew (Indonesian Journal of Social Research (IJSR), 2025)
Postgraduate students, particularly those lacking exposure to scholarly learning, have to confront significant financial shortages, which delay the attainment of their academic objectives. This study explores the factors that motivate young people to get master's degrees and the challenges students face during their postgraduate journey at South Africa's historically disadvantaged universities. Data were collected and processed using a qualitative research method. The study employed purposive sampling and a snowball sample to select participants. Thematic analysis was employed to scrutinize the data. The study revealed that augmented employment prospects, enhancement of remunerative status, familial heritage, and aspiration for scholarly attainment are the factors motivating young people to pursue postgraduate studies. The challenges of insufficient supervision and limited familial support have been identified. The study recommends that the higher education sector seek financial support from external sources, including foreign donors and the private sector, to address some of the challenges young scholars experience during their postgraduate studies and encourage the pursuit of master's degrees. Additionally, it is advised that supervisors receive appropriate training in adequate student support.